Durability of Immune Responses After Boosting in Ad26.COV2.S-Primed Healthcare Workers. (15th July 2022) - Sablerolles, Roos S G; Rietdijk, Wim J R; Goorhuis, Abraham; Postma, Douwe F; Visser, Leo G; Schmitz, Katharina S; Geers, Daryl; Bogers, Susanne; van Haren, Eva; Koopmans, Marion P G; Dalm, Virgil A S H; Kootstra, Neeltje A; et al.
Abstract: The emergence of SARS-CoV-2 variants raised questions regarding the durability of immune responses after homologous or heterologous boosters after Ad26.COV2.S-priming. We found that SARS-CoV-2–specific binding antibodies, neutralizing antibodies, and T cells are detectable 5 months after boosting, although waning of antibodies and limited cross-reactivity with Omicron BA.1 was observed.